Adsorption Study of Methylene Blue and Methyl Red on Activated Carbon from Silver Composite Using the Extract of Spent Coffee Grounds - Haidar Sitie Rafidah; Hafiizh Prasetia; Asep Saefumillah (Jurnal Sains Materi Indonesia, 2024)
The activated carbon was prepared from silver composite via an extract of spent coffee grounds with phosphoric acid activation. The activated carbon was used to study the removal of methylene blue and methyl red from an aqueous medium. Fourier-transform infrared spectroscopy (FTIR) spectra confirmed the functional group of O–P–O that can interact with dye molecules and the reduction process of Ag+ to Ag0. Field Emission Scanning Electron Microscopy (FESEM) morphology suggests a porous and irregular polygonal shape. The efficiency removal and adsorption capacity of methylene blue reached 98.73% and 9.87 mg/g at pH 9, while methyl red reached 98.55% and 9.86 mg/g at pH 4. The kinetics adsorption study followed the pseudo-first order. The isotherm adsorption study followed the Langmuir model. Based on the kinetics and isotherm study, the adsorption study of methylene blue and methyl red is chemical sorption.